Contrasting Inflammation Resolution during Atherosclerosis and Post Myocardial Infarction at the Level of Monocyte/Macrophage Phagocytic Clearance - Thorp, Edward (Frontiers in Immunology, 2012)
In cardiovascular disorders including advanced atherosclerosis and myocardial infarction (MI), increased cell death and tissue destabilization is associated with recruitment of inflammatory monocyte subsets that give rise to differentiated macrophages. These phagocytic cells clear necrotic and apoptotic bodies and promote inflammation resolution and tissue remodeling. The capacity of macrophages for phagocytosis of apoptotic cells (efferocytosis), clearance of necrotic cell debris, and repair of damaged tissue are challenged and modulated by local cell stressors that include increased protease activity, oxidative stress, and hypoxia. The effectiveness, or lack thereof, of phagocyte-mediated clearance, in turn is linked to active inflammation resolution signaling pathways, susceptibility to atherothrombosis and potentially, adverse post MI cardiac remodeling leading to heart failure. Previous reports indicate that in advanced atherosclerosis, defective efferocytosis is associated with atherosclerotic plaque destabilization. Post MI, the role of phagocytes and clearance in the heart is less appreciated. Herein we contrast the roles of efferocytosis in atherosclerosis and post MI and focus on how targeted modulation of clearance and accompanying resolution and reparative signaling may be a strategy to prevent heart failure post MI.